High-throughput multiplexed gene and cell doping analysis through CRISPR-Cas12a system integrated with blood direct PCR - Yi, Joon-Yeop; Choi, Hyomin; Kim, Minyoung; Jeong, Yujin; Hahn, Ji-Sook; Son, Boram; Park, Hee Ho; Sung, Changmin (American Association for the Advancement of Science, 2025)
Advancements in gene and cell therapies introduce "gene and cell doping," requiring efficient and sensitive detection methods. Here, we report a high-throughput multiplexed gene and cell doping analysis (HiMDA) using CRISPR-Cas12a system integrated with blood direct polymerase chain reaction (PCR). Blood direct PCR enables simultaneous amplification of multiple exogenous genes directly from whole-blood samples. Coupled with sequence-specific DNA recognition and fluorescence reporter system, HiMDA achieves multiplexed, on-target detection of doping genes and cells. Our results demonstrate HiMDA's feasibility with only 5 microliters of blood required for the entire 90-minute process. HiMDA exhibits exceptional sensitivity, detecting as few as 2.5 copies of doping target genes from blood-four times more sensitive than current anti-doping standards-and identifying in vivo doping up to 10 days. These findings highlight HiMDA's robust high-throughput, multiplexed capabilities, satisfying the sensitivity and selectivity demands of anti-doping research. HiMDA offers a flexible solution to meet future doping detection challenges.